Chemical Exposure Levels in Printing Workers with Cholangiocarcinoma. Issue 5 (22nd November 2014) - Yamada, Kenichi; Kumagai, Shinji; Nagoya, Toshio; Endo, Ginji
Abstract : Chemical Exposure Levels in Printing Workers with Cholangiocarcinoma: Kenichi YAMADA, et al . Occupational Health Research and Development Center, Japan Industrial Safety and Health Association— Objective: This study aimed to identify chemicals used by printing workers with cholangiocarcinoma, as well as the levels of exposure to the chemicals. Methods: Information necessary to identify chemicals used by printing workers with cholangiocarcinoma and to estimate chemical exposure concentrations was obtained from the Ministry of Health, Labour and Welfare, Japan. Working environment concentrations of the chemicals in the printing rooms were estimated using a well‐mixed model, and exposure concentrations during the ink removal operation were estimated using a near‐field and far‐field model. Shift timeweighted averages (TWA) of exposure concentrations were also calculated. Results: Two workers from each of three small printing plants examined suffered from cholangiocarcinoma, and all six of these workers had been exposed to 1, 2‐dichloropropane (1, 2‐DCP) for 10−16 years. The estimated working environment concentrations of 1, 2‐DCP in the printing rooms were 17−180 ppm and estimated exposure concentrations during the ink removal operation were 150−620 ppm. Shift TWA values were estimated to be 62−240 ppm. Four of the six workers had also been exposed to dichloromethane (DCM) at estimated working environment concentrations of 0−98 ppm and estimated exposure concentrations during the ink removal operation of 0−560 ppm. Shift TWA values were estimated to be 0−180 ppm. Other chlorinated organic solvents (1, 1, 1trichloroethane, 1, 1‐dichloro‐1‐fluoroethane) and petroleum solvents (gasoline, naphtha, mineral spirit, mineral oil, kerosene) were also used in the ink removal operation. Conclusions: All six printing workers with cholangiocarcinoma were exposed to very high levels of 1, 2‐DCP for a long term.